Job stress level among non-academic staff in school of health sciences at Universiti Sains Malaysia (USM) health campus - Nizar, Nur Zulaikha Azra Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Job-related stress happens where work demands of various aspects and combinations exceed the person's capacity and capability to cope. Job-related stress can be due to numerous events to the employee. The objective of this study is to determine job stress levels and health conditions among non-academic staff in the School of Health Sciences. A cross-sectional study was conducted on 98 non-academic staff in Scholl of Health Sciences by using a self-administered questionnaire. The data were analyzed by using SPSS 26.0. Mann Whitney Test was used to determine the difference between age and job stress level. In addition, Pearson Chi-Square was used to determine the association between gender, marital status, and years of working experience with stress level, and the Pearson Correlation Test was used to determine the relationship between job stress level and stress symptoms among non-academic staff in School of Health Sciences. The findings of this study showed that the overall mean stress level among nonacademic stress was at a low level (M=54.89, SD=11.667). Overall, it appeared most (100%) of the non-academic staffs’ health conditions were not affected. Besides, there is no significant difference between age and stress level among non-academic staff (p=0.323). Furthermore, there is no significant association between gender (p=0.082), marital status(p=0.703), and years of experience (p=0.919) and job stress level among non-academic staff in the School of Health Sciences, USM. The study also found that there is a strong and positive relationship between job stress level and stress symptoms among non-academic staff (p=0.001, r=+0.544). In conclusion, non-academic staff at the School of Health Sciences had a low level of job stress and good health condition.